Legalitas Penutupan Selat Hormuz oleh Iran dalam Hukum Internasional dan Perspektif Siyāsah Dauliyyah: Studi atas Eskalasi Konflik Tahun 2026 - Ramadhinzaghi Alby Siregar; Akmaluddin Syahputra (CV Global Research Publication, 2026)
Iran's decision to close the Strait of Hormuz in response to United States economic sanctions has raised significant legal questions concerning the permissibility of such an action under international law. This study aims to analyze the legality of Iran's closure of the Strait of Hormuz from the perspective of International Law of the Sea and the principles of fiqh siyāsah dauliyyah. This research employs a normative legal research method using statutory and conceptual approaches. The legal materials consist of primary, secondary, and tertiary sources, which are analyzed qualitatively through library research and legal interpretation. The findings indicate that the closure of the Strait of Hormuz lacks legal justification under International Law because it contradicts the 1958 Convention on the Territorial Sea and the Contiguous Zone, the principle of pacta sunt servanda, the transit passage regime, and the Articles on Responsibility of States for Internationally Wrongful Acts (ARSIWA) 2001. From the perspective of fiqh siyāsah dauliyyah, such action also violates the principles of al-wafā' bi al-'aqd, lā ḍarar wa lā ḍirār, and maṣlaḥah mursalah , as it disregards the obligation to honor international agreements and causes widespread harm to the international community. This study concludes that both International Law of the Sea and fiqh siyāsah dauliyyah converge in considering the closure of the Strait of Hormuz as legally unjustifiable, demonstrating that both legal systems complement one another in providing normative legitimacy for the protection of international navigational freedom.